OPTIMIZATION OF PLANTING GEOMETRY AND HAULM KILLING DAYS FOR INCREASING PRODUCTION OF SEED SIZE TUBERS IN POTATO - jagannath, murlidhar sadawarti (Potato Journal, 2022)
A field experiment was conducted for two consecutive years 2018-19 and 2019-20 with high bulking early potatocultivar Kufri Khyati at Central Potato Research Institute, RS, Gwalior in split plot design with six planting geometriesas main plots viz S1-60√20 cm (Control), S2-66√15 cm, S3-66√20 cm, S4-75 √15 cm, S5-75√20 cm and S6-paired row and threehaulm killing dates as sub plots viz 70, 80 and 90 days after planting. For growth parameters, only planting geometry 66√15cm recorded significantly higher plant height (52.6 cm) over other planting geometries.75√15 cm (52.6) and 75√20 cm (50.2)planting geometry recorded non significant but higher compound leaves/plant over other plant geometries. Days to haulmkilling did not influence the growth parameters viz, stem, compound leaves and plant height. Significant increasing trendwas recorded for number and weight of seed size and total tubers with increasing planting geometry over wider plantgeometry 75√20 cm (285 thousand/ha, 17.41 t/ha seed size tuber and 671 thousand/ha, 34.52 t/ha for total tuber) and highestwas recorded in paired row planting (487 thousand/ha, 29.52 t/ha seed size tuber and 1040 thousand/ha, 45.93 t/ha totaltuber). Paired row planting with 70 days of haulm killing recorded significantly highest seed size (516 thousand/ha) andtotal tuber number (1092 thousand/ha). By number 60√20 cm planting geometry at 80 days of haulm killing (51.15% and0.957) and by weight paired row planting at 70 days of haulm killing (73.15% and 0.367) recorded significantly highest seedsize tubers percent and best seed: non seed ratio over other factor combinations. Planting geometry 66√15 cm at 80 dayshaulm killing (11.3) and 75√15 cm at 90 days of haulm killing (11.7) recorded significantly highest seed multiplication rateby number and weight respectively. Paired row planting with 70 days haulm killing gave highest seed size tuber yield, percent seed size tuber and best seed: non seed ratio but planting geometry with 66√20 cm and haulm killing at 70 days foundto be economically viable option for the farmers with higher B:C ratio (1.75) for seed production of variety Kufri Khyati.